2012
DOI: 10.1093/jmicro/dfs052
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of sclerostin synthesized by osteocytes in relation to bone remodeling in the interradicular septa of ovariectomized rats

Abstract: This study aimed to elucidate whether estrogen deficiency would affect the synthesis of an osteocyte-derived factor, sclerostin, in the mesial region of alveolar bone. Eight 9-week-old Wister female rats were ovariectomized (OVX), and the other eight rats were Sham-operated (Sham). After 4 weeks, the interradicular septa of mandibular first molar were embedded in paraffin, and then, were histochemically examined. Sclerostin-positive osteocytes were located in a superficial layer of the mesial region of Sham bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…2) The anti-mouse sclerostin antibody was identical to that used in other studies using rat models. 20,38 This and previous studies showed weak sclerostin labeling of osteocytes in normal periodontium. However, in another study, normal periodontium of mice showed strong sclerostin expression in osteocytes using anti-mouse sclerostin antibody.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…2) The anti-mouse sclerostin antibody was identical to that used in other studies using rat models. 20,38 This and previous studies showed weak sclerostin labeling of osteocytes in normal periodontium. However, in another study, normal periodontium of mice showed strong sclerostin expression in osteocytes using anti-mouse sclerostin antibody.…”
Section: Discussionsupporting
confidence: 69%
“…1) Increased RANKL‐positive cells, including PDL cells, osteoblasts, and inflammatory cells, were found in the PDL area before day 10 (data not shown); however, the relative contribution of RANKL sources between those cells and osteocytes was not determined. 2) The anti‐mouse sclerostin antibody was identical to that used in other studies using rat models 20,38 . This and previous studies showed weak sclerostin labeling of osteocytes in normal periodontium.…”
Section: Discussionmentioning
confidence: 70%